Revitalisasi SMK Melalui Studi Komparasi ke Selandia Baru - Eko Mulyadi (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Comparative Study to New Zealand conducted by Director General GTK on 16 October to November 2017 in order to implement Inpres No. 9 year 2016 on the revitalization of vocational schools, by developing the educator human resources productive teachers to be more competent, skilled and can make the network, especially best teaching practices. By observing, understanding the educational system, effective, efficient, and the way teachers teach with Inquiry learning, Project base learning, Collaborative learning and application of IT both in class and out of class in New Zealand make a source of inspiration that can be applied in Indonesia.